2018
DOI: 10.1177/0734016818767727
|View full text |Cite
|
Sign up to set email alerts
|

Polyvictimization and Sexual Risk Behaviors in College-Aged Women

Abstract: Current research suggests a link between childhood sexual abuse and risky sexual behaviors (RSBs) in emerging adults. However, previous studies neglect evaluating the influence of high levels of cumulative childhood victimization. The present study examined the relationships among polyvictimization, six aggregate categories of childhood victimization, and RSB in college women. This study first examined the relative contributions of polyvictimization and individual categories of childhood victimization in predi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…This oversight is a missed opportunity to understand women's lived experiences, which may include the sequential or co-occurrence of various forms of GBV by age 24 years. The impact of sequential and/or concurrent GBV may differ than that of single GBV exposures (Alexander, Amerigo, & Harrelson, 2018). The timing of exposure also may matter; for instance, the SRH effects of IPV before versus during pregnancy may differ (Islam, Broidy, Mazerolle, Baird, & Mazumder, 2018).…”
Section: Scope Of Gbv Exposuresmentioning
confidence: 99%
“…This oversight is a missed opportunity to understand women's lived experiences, which may include the sequential or co-occurrence of various forms of GBV by age 24 years. The impact of sequential and/or concurrent GBV may differ than that of single GBV exposures (Alexander, Amerigo, & Harrelson, 2018). The timing of exposure also may matter; for instance, the SRH effects of IPV before versus during pregnancy may differ (Islam, Broidy, Mazerolle, Baird, & Mazumder, 2018).…”
Section: Scope Of Gbv Exposuresmentioning
confidence: 99%
“…Even when university/college-aged adults were studied, the main concern was the effect of childhood multiple victimizations on current behavior. For example, Alexander, Amerigo, and Harrelson (2018) found that polyvictimization was the best predictor of what they termed "risky sexual behavior" among postsecondary school women (p. 345), whereas Espelage, Hong, and Mebane (2016) and Holt et al (2017) found childhood polyvictimization related to current psychological functioning among such students.…”
Section: Polyvictimization In the Lives Of Female Postsecondary School Students: What Do We Know And How Do We Know It?mentioning
confidence: 99%
“…Also drawing from a developmental perspective, Alexander, Serrano-Amerigo, and Harrelson (2018) shed important light on the relationship between childhood polyvictimization and maladaptive life outcomes. In their study of college women in a U.S. Southern state, the authors examine whether experiencing multiple forms of victimization in childhood (i.e., polyvictimization) leads to risky sexual behaviors in early adulthood.…”
mentioning
confidence: 99%